Pengaruh Pendidikan Kesehatan Kehamilan Resiko Tinggi terhadap Tingkat Pengetahuan Ibu Hamil di PMB Syarifah Mranggen Demak - Fara Aurelia Putri; Nella Vallen; Kristina Maharani (Pusat Riset dan Inovasi Nasional, 2025)
One way to prevent high-risk pregnancies is by addressing the lack of knowledge. The Pre-Experimental Design research aims to determine how high-risk pregnancy health education impacts pregnant women's knowledge about their condition, using a one-group pretest-posttest design. By providing books and videos once, this research conducted an intervention. Data was collected through pre-test and post-test questionnaires. The total sampling method was used to collect 45 respondents. The results of the data analysis indicate that the normality test before and after the intervention showed that the data is not normally distributed with a significance of 0.00 ≤ 0.05. To test the research hypothesis, the Wilcoxon test was used, and the results showed that the Asymp. Sig. (2-tailed) value is 0.000 ≤ 0.05, which indicates that Ho is rejected and Ha is accepted. It can be concluded that health education on high-risk pregnancy shows that health institutions should implement and provide health education about high-risk pregnancy to patients who are already aware as well as those who are not. This will help pregnant women become more informed and reduce the number of high-risk pregnancies.